The effect of targeted rheumatoid arthritis therapeutics on systemic inflammation and anemia: analysis of data from the CorEvitas RA registry - Anthony S. Padula; Dimitrios A. Pappas; Stefano Fiore; Taylor S. Blachley; Kerri Ford; Kelechi Emeanuru; Joel M. Kremer (Arthritis Research & Therapy, 2022)
Abstract Background To evaluate the effects of tumor necrosis factor inhibitors (TNFi), interleukin-6 receptor inhibitors (IL-6Ri), and Janus kinase inhibitors (JAKi) on hemoglobin (Hb) and C-reactive protein (CRP) levels in adults enrolled in CorEvitas (formerly Corrona), a large US rheumatoid arthritis (RA) registry. Methods Patients who initiated TNFi, IL-6Ri, or JAKi treatment during or after January 2010, had Hb and CRP measurements at baseline and 6-month follow-up (± 3 months) and had continued therapy at least until that follow-up, through March 2020, were included in the analysis. Changes in Hb and CRP were assessed at month 6. Abnormal Hb was defined as < 12 g/dL (women) or < 13 g/dL (men); abnormal CRP was ≥ 0.8 mg/dL. Differences in Hb and CRP levels were evaluated using multivariable regression. Results Of 2772 patients (TNFi, 65%; IL-6Ri, 17%; JAKi, 17%) evaluated, 1044 (38%) had abnormal Hb or CRP at initiation; an additional 252 (9%) had both abnormal Hb and CRP. At month 6, the IL-6Ri group had a greater Hb increase than the TNFi (mean difference in effect on Hb: 0.28 g/dL; 95% CI 0.19–0.38) and JAKi (mean difference in effect on Hb: 0.47 g/dL; 95% CI 0.35–0.58) groups, regardless of baseline Hb status (both p < 0.001). The CRP decrease at month 6 was greater with IL-6Ri compared with TNFi and JAKi, regardless of baseline CRP status (both p < 0.05). Conclusion These real-world results align with the mechanism of IL-6R inhibition and may inform treatment decisions for patients with RA.